Teaching EFL in a Rural Context through Place-Based Education: Expressing Our Place Experiences through Short Poems - Salazar Jaramillo, Pilar; Espejo Malagon, Yeyson (European Journal of Sustainable Development, 2019)
This project implemented Place Based Education (PBE) as the basis to teach English to children from a rural school in Bogota, Colombia. Place Based Education is defined by (Sobel, 2004) as the process of considering not only the community, but also the environment as the beginning to teach concepts related to language arts and other subjects from the curriculum. In the case of our research project; we used PBE to teach English as a Foreign Language to two fourth grade rural classrooms. As for the objectives of our research, the first one sought to explore the role PBE had on approaching EFL students to their rural context and as for the second one, it was aimed to identify and describe the responses students had towards the writing of short poems based on the Genre-Based Approach (Hyland, 2007). Regarding the findings of our research project, it was evidenced that Place Based Education connected students to their rural surroundings and developed on them, an emotional bond towards their rural world. Regarding the writing of English, it was shown that the Genre- Based Approach permitted for students to feel confident and enthusiastic while writing in English. Furthermore, as part of the experiences students had with their local and English language, a book with the poems written by the students was created and published. Key words: Place Based Education, Genre- Based Approach, poetry for children, rural context, EFL